Samarium Triflate Catalyzed Efficient Synthesis of Quinoxalines - Raghuveerachary, P.; Devanna, N. (Asian Journal of Chemistry, 2010)
A highly efficient method for the synthesis of quinoxalines derivatives has been developed using samarium triflate as catalyst. The method is applicable to a variety of 1,2-diketones and 1,2-diamines to afford the corresponding quinoxalines derivatives in high yields. All the reactions were carried out at acetonitrile reflux.